The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2002
DOI: 10.1109/16.992867
|View full text |Cite
|
Sign up to set email alerts
|

Technology and reliability constrained future copper interconnects. I. Resistance modeling

Abstract: A realistic assessment of future interconnect performance is addressed, specifically, by modeling copper (Cu) wire effective resistivity in the light of technological and reliability constraints. The scaling-induced rise in resistance in the future may be significantly exacerbated due to an increase in Cu resistivity itself, through both electron surface scattering and diffusion barrier effect. The impact of these effects on resistivity is modeled under various technological conditions and constraints. These c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
97
1
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(102 citation statements)
references
References 12 publications
1
97
1
3
Order By: Relevance
“…And the remainder have an average characteristic dimension of b i = l+d 2 , which can lead to some decrease of conductivity. Thus, the coefficient Λ may be even smaller than is given in the tables in [8], if the surface roughness and grain size of metal inclusion are taken into account [9][10][11]. For our computations, we assume that a reasonable value is Λ = 0.8, corresponding to a 20% decrease in conductivity.…”
Section: Conductivity Taking Into Account Small Size Of Nanorods Compmentioning
confidence: 99%
“…And the remainder have an average characteristic dimension of b i = l+d 2 , which can lead to some decrease of conductivity. Thus, the coefficient Λ may be even smaller than is given in the tables in [8], if the surface roughness and grain size of metal inclusion are taken into account [9][10][11]. For our computations, we assume that a reasonable value is Λ = 0.8, corresponding to a 20% decrease in conductivity.…”
Section: Conductivity Taking Into Account Small Size Of Nanorods Compmentioning
confidence: 99%
“…These approaches assume a ratio p of carrier collisions with the surface reflect specularly, while 1−p scatter diffusely. Such theories can be fit to experiment with p as a free parameter, but do not provide insight into how to improve conductivity.More recently, surface roughness scattering has raised the attention of researchers in industry [5,6,7], and quantum mechanical approaches to surface scattering calculations have been proposed. The two primary approaches include the Kubo linear response theory of Tesanović et al [8] and Trivedi and Ashcroft [9], and the diagrammatic Keldysh formalism of Meyerovich and collaborators [10,11,12].…”
mentioning
confidence: 99%
“…However, all of these barrier materials are at least one order of magnitude more resistive than Cu itself. 4 Thus, to lower the overall line resistance, it is essential to maximize the Cu volume in its damascene trench, which requires the thickness of the barrier material to be reduced as much as possible. Conversely, it has been found that conventional barrier materials lose their capability of blocking Cu diffusion when their thicknesses are scaled below~3 nm, as illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%